THE INFLUENCE OF PROFESSIONALISM, JOB SATISFACTION, AND PROFESSION ETHIC OF AUDITOR ON AUDIT QUALITY OF FINANCIAL REPORT (A STUDY ON AUDITOR WORKED IN PUBLIC ACCOUNTING FIRM AT BANDA ACEH AND MEDAN CITIES) - Qorry Nitty; M. Rizal Yahya (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The purposes of this study is to determine the influence of professionalism, job satisfaction, and profession ethic of auditors on audit quality of financial report at public accounting firm in Banda Aceh and Medan cities. The data used are secondary data from list of a names public accounting firm and the primary data in the form of respondent's answer from questionnaire data collection. This study taken non-probability sampling which was convenience sampling. The population are the auditors who worked at public accounting firm. This study used multiple linear regression analysis for the data analysis technique, in which the result showed that professionalism, and profession ethic simultaneously affect auditors on audit quality. Partially, only the job satisfaction of auditor does not influence audit quality.